Design of formulated products integrating heuristic knowledge and consumer assessment. Issue 4 (23rd December 2020) - Arrieta‐Escobar, Javier A.; Camargo, Mauricio; Morel, Laure; Bernardo, Fernando P.; Orjuela, Alvaro; Wendling, Laurent
Abstract: This work proposes a systematic approach for the design of formulated products incorporating consumer assessment and heuristic knowledge. The methodology is divided into two main phases: Consumer assessment and product realization. In the first part, product attributes valued by consumers and their interactions are identified through usability tests performed on a reference product, and fuzzy integral analysis. In the second phase, alternative product formulations are generated using a mixed‐integer optimization approach, which incorporates heuristic rules regarding the choice of ingredients and their amounts. The results from the consumer assessment phase are transformed into additional heuristics and incorporated into the design. Different alternative formulations are generated at a lab‐scale, by using two commercial skin moisturizers as references. Those formulations that included additional heuristics are shown to be more similar to the references. As a result, the incorporation of consumer preferences significantly reduced the time and resources spent on the design process.